Integrated Profiling of Fatty Acids, Sterols and Phenolic Compounds in Tree and Herbaceous Peony Seed Oils: Marker Screening for New Resources of Vegetable Oil - Xiaoqin Wang; Chunhuan Li; María del Mar Contreras; Vito Verardo; Ana María Gómez-Caravaca; Chen Xing (Foods, 2020)
Tree peonies (Paeonia ostii and Paeonia rockii) are popular ornamental plants. Moreover, these plants have become oil crops in recent years. However, there are limited compositional studies focused on fatty acids. Therefore, this work aims to reveal compositional characteristics, regarding fatty acids, sterols, γ-tocopherol and phenolic compounds, of tree peony seed oils from all major cultivation areas in China, and to compare with herbaceous peony seed oil. For that, an integrative analysis was performed by GC-FID, GC-MS and UHPLC-Q-TOF-MS technologies. The main fatty acid was α-linolenic acid (39.0–48.3%), while β-sitosterol (1802.5–2793.7 mg/kg) and fucosterol (682.2–1225.1 mg/kg) were the dominant phytosterols. Importantly, 34 phenolic compounds, including paeonol and “Paeonia glycosides” (36.62–103.17 μg/g), were characterized in vegetable oils for the first time. Conclusively, this work gives new insights into the phytochemical composition of peony seed oil and reveals the presence of bioactive compounds, including “Paeonia glycosides”.